PERAN KELUARGA DALAM PENGENDALIAN DIRI MANTAN PECANDU NARKOBA - Andi syahraeni (Jurusan Bimbingan dan Penyuluhan Islam, 2023)
The thing that needs to be understood by the families of ex-addicts is that someone who uses drugs is a victim, and it could be that one of the motivations for someone to use drugs is caused by their own family. For example, due to the divorce of parents so that the child becomes a broken home which makes the child stressed so that he makes drugs as an escape. It could also be due to parenting patterns given by parents to children, and so on. But that is only one of the factors a person uses drugs, there are still very many factors that can influence someone to use drugs such as association, ignorance or being trapped, trial and error, and many more. There are many efforts that can be made by families to help former drug addicts control their desire not to use drugs again. During rehabilitation, the National Narcotics Agency (BNN) also provides a program for resident families that aims to understand the resident family what kind of treatment needs to be given to former addicts after rehabilitation. This is intended so that the rehabilitation process is sustainable in their respective families. So in this case the family needs to be provided with provisions to control and what to do if a former addict collapses.